Shear strength improvement of peat soil due to consolidation - Anggraini, Vivi (2006)
One major problem related to construction on peat deposit is the low shear strength of the soil. However previous researches have shown that the shear strength could increase significantly upon consolidation and hence some improvement methods have been developed to increase the bearing capacity of the peat deposit by utilizing consolidation pressure. The aim of this project is to evaluate the increase of shear strength of fibrous peat due to application of consolidation pressure. The initial undrained shear strength was obtained from vane shear test in-situ. For this study, samples were prepared under several consolidation pressures: 50 kPa, 100 kPa, 150 kPa, and 200 kPa. The shear strength of the samples was obtained by triaxial compression test under unconsolidated undrained condition. The results proved that there is an increase in shear strength due to application of consolidation pressure. The initial shear strength predicted based on the equation developed for the results of Triaxial testing agreed with the in-situ strength obtained by field vane shear test, however the ratio of strength increase for peat in this study is 0.06 which is very low as compared to published data.